2019
DOI: 10.1080/13218719.2018.1485525
|View full text |Cite
|
Sign up to set email alerts
|

Financial and caregivers’ stressors in Australian law students – a qualitative analysis

Abstract: Australian law students exhibit high levels of psychological distress compared to the general population. In 2013, The University of Sydney Law School conducted a survey to examine the level of distress in students, what factors were associated with their distress and what strategies might mitigate student distress. This article reports on the survey's qualitative findings relating to financial stressors and care-giving responsibilities. The findings provide further insights into the context of financial stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Specific to working students, work-study balance is associated with better academic performance (Tetteh & Attiogbe, 2019), wellbeing (Lenaghan & Sengupta, 2007), and satisfaction (Buda & Lenaghan, 2005). In Australia, lack of balance between work and study has been cited as a key factor in students deferring their study or withdrawing (Burns et al, 2019) and experiencing burnout (Moore & Loosemore, 2014). Thus, as students improve the balance between their work and study, they should be more satisfied academically.…”
Section: Outcomes Of Boundary Work: Work-study Balance and Academic S...mentioning
confidence: 99%
“…Specific to working students, work-study balance is associated with better academic performance (Tetteh & Attiogbe, 2019), wellbeing (Lenaghan & Sengupta, 2007), and satisfaction (Buda & Lenaghan, 2005). In Australia, lack of balance between work and study has been cited as a key factor in students deferring their study or withdrawing (Burns et al, 2019) and experiencing burnout (Moore & Loosemore, 2014). Thus, as students improve the balance between their work and study, they should be more satisfied academically.…”
Section: Outcomes Of Boundary Work: Work-study Balance and Academic S...mentioning
confidence: 99%
“…It has highlighted that caring responsibilities can influence students' decisions and experiences within higher education. For instance, student carers' choices of what and where to study have been found to be linked to their caring role, and many sacrificed elements of the student experience, such as social events, to provide better care (Burns et al, 2019). Research has also identified that student carers may experience lower wellbeing than those without caring responsibilities (Day, 2019;Hussain, 2011;NUS, 2015), and face increased financial strain (NUS, 2015).…”
Section: Introductionmentioning
confidence: 99%